MANAJEMEN PESERTA DIDIK - Sya'ban, Riska; Darmawati, Darmawati (STKIP Pesisir Selatan, 2025)
This research aimed to determine how student management was able to serve as a media for improving the quality and achievement of Islamic shcool. Proper and effective management of students allowed for measurable educational outcome within the institution. Student management involves systematic effort to organize students from their initial admission until graduation, including activities such as planning, coaching, and evaluation. Furthermore, the objective of this research was to analyze student management at Madrasah Tsanawiyah Al-Mubarak Marisa, Pohuwato. Then, this study employed a qualitative research method with a phenomenological approach, focusing on understanding real-life phenomena within the school environment. In addition, technique data collections were used in this research through observation, interview, and documentation. In conclusion, the research findings stated that Madrasah Tsanawiyah Al-Mubarak Marisa, Pohuwato was established 18 years ago, has successfully developed excellent students through effective student management processes encompassing planning, student development, and evaluation activities.